Description of a new soft scale insect of the genus Pulvinaria Targioni Tozzetti (Hemiptera: Coccomorpha: Coccidae) from India - Talukder, Bipradeb; Das, Bijan Kumar (Zootaxa, 2021)
A new soft scale species (Hemiptera: Coccomorpha: Coccidae), Pulvinaria kalyaniensis Talukder & Das, sp. n., is described from specimens collected on twigs of Azadirachta indica A. Juss. (Meliaceae) from Kalyani, West Bengal, India. This new species is similar to P. aligarhensis Avasthi & Shafee and P. ixorae Green, but can be distinguished by different character states of dorsal areolations, submarginal tubercles, dorsal tubular ducts, the number of prevulvar setae and the number of loculi in each multilocular pore. An updated identification key to the species of Pulvinaria Targioni Tozzetti found in India is provided.